Resiliência: análise das estratégias de enfrentamento de pacientes em tratamento radioterápico - Paula Junior, Wanderley de (2009)
This study presents a theorical review and an empirical inquiry on subjects: resilience, coping, stress and subjective well-being. The bibliographical review is presented on chapter 1 after a deep investigation and intense researches on articles and books about the subject above quoted. In chapter 2 and 3 it s presented the articles about the research done with 60 patients in radiotherapy treatment. In the first article the goal was to describe the ways patients faced the treatment and also to have a perception of the subjective well-being according to the discussion of resilience. In the second article the objective was to analyse the relationship among coping, resilience and subjective well-being. The results of this inquiry showed the social support, especially the family, the religion and the individual characteristics, as their main support when it comes to facing the illness and its treatment. In the coping strategies, the patients reported having used more the approach strategies (M = 38,64 and DP = 9,66) rather than the avoiding one (M = 26 and DP = 7,89). About the well-being , the participants reported a better positive affection, better satisfaction with life rather than the negative affection and less insatisfaction with life. To the stress symptoms the highest score was to the phycological ones (M = 16,13 and DP = 11, 13) instead of the physical (M =11,69 and DP = 5, 98). The numbers showed important information when they said that the approach strategies, focused on the problem, may be related to the emotional adjustment and also to the subjective well-being.